INTEGRATING THE MEANING OF LIFE AND MENTAL HEALTH EDUCATION THROUGH THE NOVEL A PORTION OF CHICKEN MIE BEFORE DIE BY BRIAN KHRISNA - Wulandari, Wulandari; Alsunah, Aditya Ansor; Nurwahidah, Lina Siti; Julianto, Cecep Dudung (Journal Of Educational Experts (JEE), 2026)
This study aims to analyze the psychological aspects of the main character in the novel Seporsi Mie Ayam Before Death by Brian Khrisna using Sigmund Freud's psychoanalytic theory as the main foundation. The method used is a qualitative approach with content analysis techniques. The focus of the research is on the interaction of Freud's three personality structures, namely id, ego, and superego in describing the inner conflicts experienced by the character. The results of the analysis show that the conflict between the instinctive impulse (id) to avoid suffering, the mechanism of self-control (ego), and moral demands or social norms (superego) form a realistic and complex psychological picture of the character. This dynamic also reveals how the characters struggle to find meaning in life in conditions of depression and existential crisis. This study shows that Freud's psychoanalytic approach is effective for the study of literary psychology in exploring mental health problems and the search for meaning in contemporary Indonesian literary works.